The relationship Between Financial Compensation and Salesperson Performance in a Sabah Retail Sector : The Mediating Role of Organizational Commitment - Toh, Pei Sung; Iklima Husna Abdul Rahim; Arsiah Bahron; Teo, Wan Lee (2018)
The Wholesale and Retail are one of the selected sectors of economic opportunity under the 12 National Key Economic Areas, especially shopping mall has become the concerns in boosting Malaysia as one of the worlds’ leading shopping destination. Apart from that, the salesperson plays a vital role in providing excellent performance in terms of services to the customers. The shopper nowadays has concerns about the customer service besides the price, quantity and quality of the product itself. It has been noting that financial compensation, such as salary and reward would able to attract and motivate employees in order to provide an excellent job performance. Furthermore, the salary and reward would influence the employees to be committed and thus, increase their performance. Therefore, the study is aimed to examine the relationship between compensation and salesperson performance. Organizational commitment is examined on the relationship between compensation and salesperson performance in the mechanism. Quantitative approach has been applied in this study by using questionnaires through a survey. The data are analysed by using the Smart PLS 3.0 software. The findings suggested that the reward had a significant relationship to salesperson performance. It also has suggested that both salary and reward have a significant relationship to organizational commitment. Lastly, the findings suggested that only normative commitment had a mediating effect on the hypothesized relationship.